On-treatment blood pressure and dose-dependent effects of ARNI in heart failure with reduced ejection fraction: Insights from a multicenter registry - Jiesuck Park; Chan Soon Park; Tae-Min Rhee; Hye Jung Choi; Hong-Mi Choi; Hyun-Jung Lee; Jun-Bean Park; Yeonyee E. Yoon; Seung-Pyo Lee; Yong-Jin Kim; Goo-Yeong Cho; Hyung-Kwan Kim; et al. (PLoS ONE, 2025)
Background Achieving target doses of angiotensin receptor-neprilysin inhibitor (ARNI) in heart failure with reduced ejection fraction (HFrEF) is often challenging due to concerns related to hypotension. This study evaluated dose-dependent effects of ARNI considering on-treatment blood pressure (BP). Methods From a multicenter HF registry, 1,097 HFrEF patients receiving ARNI for ≥6 months were stratified into low-dose (<100 mg/day, n = 249) and intermediate-to-high-dose (≥100 mg/day, n = 848) groups. Echocardiographic changes and clinical outcomes were compared across groups, considering on-treatment BP profiles (high-BP ≥ 110 mmHg vs. low-BP < 110 mmHg). Results Low on-treatment BP was independently associated with low-dose ARNI use. Both dose groups showed echocardiographic improvement, but the intermediate-to-high-dose group had more pronounced changes. Over 3.1 years (median follow-up), low-dose ARNI use was associated with a higher risk of mortality compared to intermediate-to-high-dose. These trends were consistently observed in both high-BP and low-BP profiles. Conclusions Low-dose ARNI use was associated with less improvement in myocardial function and worse clinical outcomes, even in patients with low-BP profiles. This highlights the importance of optimal ARNI dose titration despite low BP concerns.